Internal and external strategic narratives of Ukraine: ways to test ideas - Snytko, Olena (Current issues of Ukrainian linguistics: theory and practice, 2025)
The article is devoted to the analysis of modern Ukrainian strategic narratives aimed at internal and external target audiences. These narratives have been or are being tested in the information space. The purpose of the article is to outline a matrix that can be used as a basis for the development of strategic narratives of our time, since strategic communication plays a key role in promoting Ukrainian state policy both in Ukraine and abroad and acts as the most important tool for informing and psychologically protecting society in the context of a tough cognitive war. It has been proven that the grand narrative in the system of internal strategic communication in Ukraine is the identity narrative. This narrative promotes the idea of the independence of the Ukrainian nation, which has won and is defending its statehood. The status of this grand narrative is conditioned by both the historical past of Ukraine (lack of statehood at many stages of the ethnic group’s development, long-term imposition of the imperial idea of the ’triune people’) and by its extremely difficult present associated with the Russian-Ukrainian war. The grand narrative of identity is embodied in the totality of its variants, the content of which can be outlined on the basis of the matrix of national identity advanced by Professor R. Marutyan. The scientist proposes to put the following main components in the basis of this concept: sacred war, sacred hero (as a collective image), anti-heroes, sacred sacrifice, ’infernal’ enemy, national dream. It is proposed to add the component ’historical memory’ to this list, because the narratives that outline the idea of historical memory provide answers to the questions ’Who are we?’ and ’Where does our language come from?’, and play an important role in combating the destructive Russian narrative of the ’triune people’. The need for successful presentation to the world raises the question of the formation and implementation of Ukraine’s external strategic narrative. The main external narrative, according to the author of the article, should be the narrative ’Ukraine and Ukrainians are OURS, enriching the countries of the civilised world’, which is implemented in a system of its own variants. They are reproduced as elements of a certain matrix: pragmatic narratives about models of social resilience of Ukrainians and the Armed Forces of Ukraine as the main actor of the nation’s indestructibility, alongside which are the best representatives of the civilised world, narratives that objectify the idea of common worldview and spiritual values, and narratives of common historical memory associated with different stages of the civilised history of mankind.